2016
DOI: 10.1111/ijfs.13109
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic and phytochemical content of Cucumis sativus seeds and study on mechanism of preservation of nutritional and quality outcomes in enriched mayonnaise

Abstract: Oxidative rancidity in food emulsions leads to a reduction in shelf life. Synthetic antioxidants are widely used in food industry to prevent the development of rancidity. The present study was focussed on investigating the antioxidant potential of Cucumis sativus seeds (CSS) and correlates these findings with mayonnaise enrichment and extends its shelf life. CSS exhibited the highest abundance in phenolic compounds (93.5 AE 0.1 mgGAE g À1 ), flavonoids (57.4 AE 0.1 mgQE g À1 ), b-carotene (19.46 AE 0.4 mg caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…As for all the foods with a high oil content, mayonnaise is susceptible to deterioration due to autooxidation of the unsaturated fats that can negatively affect physicochemical and sensorial attributes of food [9]. Lipid oxidation in mayonnaise causes the development of potentially toxic reaction products, undesirable off-flavors and, simultaneously, it decreases the shelf life of mayonnaise [10,11]. In order to manage these problems, various strategies can be used for avoiding or reduce oxidative processes.…”
Section: Introductionmentioning
confidence: 99%
“…As for all the foods with a high oil content, mayonnaise is susceptible to deterioration due to autooxidation of the unsaturated fats that can negatively affect physicochemical and sensorial attributes of food [9]. Lipid oxidation in mayonnaise causes the development of potentially toxic reaction products, undesirable off-flavors and, simultaneously, it decreases the shelf life of mayonnaise [10,11]. In order to manage these problems, various strategies can be used for avoiding or reduce oxidative processes.…”
Section: Introductionmentioning
confidence: 99%
“…These radicals are reacting with many hydrogen donors such as polyphenols to form steady and stable molecules and trigger color reducing of test solutions. The level of discoloration indicated that the scavenging capability of the polyphenols due to the donation of hydrogen proton (Azhagu Saravana Babu et al, 2016). The results were agreement with Alshehry et al (2021) and provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Dried powdered sample (10 g) was mixed with 200 ml of different solvents (water (65°C), ethanol (50%), and methanol (50%) and kept for 12 hr in vibratory shaker (LabortechnikGmbh, Germany) at 200 rpm. After centrifugation (6,000 g , for 15 min), the extract was filtered with microfiltration unit using polyacrylonitrile membrane, then the extracted samples were stored away from light at ̶ 20°C till the investigation is done (Azhagu Saravana Babu et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…C. sativus seed and fruit contain volatile oil, fixed oil, flavones, steroids, flavonoids, tannins, phytosterols, saponin, cucurbitacins, and alkaloids [6,12,25]. The medicinal plants with similar phytochemical profiles exhibited a therapeutic potential for treating gastrointestinal and respiratory ailments [26].…”
Section: Introductionmentioning
confidence: 99%